2015
DOI: 10.2522/ptj.20130386
|View full text |Cite
|
Sign up to set email alerts
|

Dual Tasking With the Timed “Up & Go” Test Improves Detection of Risk of Falls in People With Parkinson Disease

Abstract: The addition of a cognitive task to the TUG enhanced the identification of fall risk in people with PD. The TUG-cognitive should be considered a component of a multifaceted fall risk assessment in people with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 29 publications
2
67
2
7
Order By: Relevance
“…According to this interpretation, it was possible that older women compensated with a slowing gait when carrying out the additional cognitive task required. The nature of the manual task that required additional motor ability rather than cognitive resources was probably not sufficiently complex to reach the threshold attention required to negatively impact the performance . The results show that the additional manual task was less demanding than the cognitive task.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to this interpretation, it was possible that older women compensated with a slowing gait when carrying out the additional cognitive task required. The nature of the manual task that required additional motor ability rather than cognitive resources was probably not sufficiently complex to reach the threshold attention required to negatively impact the performance . The results show that the additional manual task was less demanding than the cognitive task.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, the results showed that the DTC in the TUGM generally required less DTC among the age groups, probably suggesting a different response strategy of the secondary tasks. These findings might suggest that the automaticity of the movements showed a greater degree of decline with cognitive task rather than with manual task . According to this interpretation, it was possible that older women compensated with a slowing gait when carrying out the additional cognitive task required.…”
Section: Discussionmentioning
confidence: 93%
“…[6][7][8][9][10][11][12] In these previous works, older adults with a higher risk of falling took longer to complete the dual-TUG test, resulting in higher DTC values. [6][7][8][9][10][11][12] However, the participants in most of those studies were frail or had a neurological disease, such as Parkinson's disease, and could be classified as lower-functioning older adults. [6][7][8][9]11,12 In contrast, most of the participants in the present study were not in the lower-functioning category.…”
Section: Discussionmentioning
confidence: 90%
“…5 Several studies have investigated the usefulness of the TUG test under the dual-task condition as a fall risk assessment, but the results have been inconsistent. [6][7][8][9][10][11][12] Additionally, potential confounders were not properly adjusted in these previous studies, because the sample sizes were too small for multivariate analyses, and the characteristics of the study participants differed widely; thus, the association between fall risk and TUG test score in the dual-task condition has not been adequately studied. [6][7][8][9][10][11][12] Furthermore, a mini-review summarizing the effectiveness of the balance tests under the dual-task condition for fall risk assessment stated that "an added value of dual balance tasks for fall prediction or assessing fall intervention effects cannot be made due to incomplete comparisons of single and dual balance tasks."…”
Section: Introductionmentioning
confidence: 99%
“…Mobility outcome measures were time (s) to complete the TUG and distance (m) covered during the 6MWT. These tests are valid and reliable in people with PD (Falvo & Earhart, 2009; Morris, Morries, & Iansek, 2001; Vance et al, 2015). …”
Section: Methodsmentioning
confidence: 99%